Pengaruh Ukuran Perusahaan, Opini Audit, Profitabilitas, dan Audit Tenure Terhadap Audit Report lag pada Perusahaan Barang dan Konsumsi Sub Sektor Farmasi yang Terdaftar di BEI Tahun 2016-2022 - Ameilia Latiefah; Sri Handayani (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze the influence of Company Size, Audit Opinion, Profitability, and Audit Tenure on Audit Report Lag in the pharmaceutical subsector consumer goods and consumer goods industry listed on the Indonesia Stock Exchange in 2016-2022. Company size is measured by Total Assets, Audit Opinion with Dummy, Profitability with Return On Assets (ROA), Audit Tenure with Total Years of Engagement. The research population consisted of 11 companies listed on the Indonesian Stock Exchange. A sample of 72 companies was selected using the saturated sample method. The results of data analysis show that simultaneously Company Size, Audit Opinion, Profitability, Audit Tenure have a significant effect on Audit Report Lag. Partially, company size has no effect on Audit Report Lag, indicating that large and small company sizes have the ability to pressure their auditors to complete audit work on time and are not a determining factor in Audit Report Lag, Audit Opinion has a partially negative effect on Audit Report Lag, shows that companies that receive an unqualified opinion from the auditor for their financial reports will tend to urge the auditor to immediately complete the audit report because an unqualified opinion is good news from the auditor. Profitability has a partial negative effect on Audit Report Lag, indicating that if a company produces a higher level of profitability, the Audit Report Lag will be shorter. Audit Tenure has a partial positive effect on Audit Report Lag, indicating that the longer the engagement between the client and the Auditor, the longer the Audit Report Lag will be.